Narratives of a sense of belonging: Perspectives from a sample of international students in South Africa - Chinyamurindi, W.T. (South African Journal of Higher Education, 2018)
South African universities have witnessed an increase in the number of international student enrolment. Strategies need to be put into place into ways of integrating and helping students develop a sense of belonging. The aim of this research (using a narrative analysis) is to understand how international students develop a sense of belonging as part of their enrolment at a rural university in the Eastern Cape Province of South Africa. In achieving this, a focus group discussion and reflective diaries were used at the start and end of the 2015 academic year using 20 international students. Data was analysed using the three levels of meaning making adopted in previous qualitative research. Three findings in the form of narratives emerge based on the data analysis. First, the formation of an in and out group mentality amongst international students. Second, the study reveals the factors that were narrated as influencing student’s sense of belonging. Despite all this, students still narrated as “suffering a sense of elsewhere”. Based on the findings and narratives generated from this work, suggestions are made that affect the work of lecturers, university administrators and also policy makers on what can be done to assist international students in developing a sense of belonging within a South African context as part of their enrolment.